THE EFFICACY OF ANTIBIOTICS IN ACUTE APPENDICITIS TREATMENT : A COMPREHENSIVE SYSTEMATIC REVIEW - Yarmansyah Putra, Reza Fahlevi; Martua H. Hrp, Surya (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Acute appendicitis has been the most common cause of lower abdominal pain leading to emergency visits worldwide. To avoid major complications, appendectomy has remained the standard treatment for uncomplicated acute appendicitis for over a century. The aim: The aim of this study to show about the efficacy of antibiotics in acute appendicitis treatment. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: The therapeutic effects of antibiotics and appendicectomy were comparable for the treatment of acute appendicitis.